(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2015)
The issue of the â€œordersâ€ in architecture covers an extremely vast field of theories, studies and design experiences that have all been developed in the framework of the architectural thinking of the Western tradition. The classical architectural orders established a stylistic canon, a code, and a language as well, in order for architectures to speak, to transmit and to signify. Generally speaking, the core issue is how architecture can create meanings. In this view, a major vehicle of sense is not the mere experience of architectural orders, but rather their transgression, their variation, up to the extreme end of disorder. Following Ludovico Quaroni, Â«The Greeks, the Etruscans, the Romans, the architects of the Romanesque, Renaissance, Baroque, Classicism made use of the orders to design as many architectures, and these were different, and even opposite one to the other [...] The orders were only components of the architectural design, that is, elements drawn from manuals that could be used and transformed in relation to the various syntactic contextsÂ». The issue of the architectural orders is therefore a partial answer to a broader question, skilfully phrased in 1886 by the twenty-two years old Heinrich WÃ¶lfflin in the introduction to Prolegomena zu einer Psychologie der Architektur, his inaugural dissertation at the Faculty of Philosophy of Munich University: Â«How is it possible that architectural forms are an expression of soul, of a StimmungÂ»? Â«I wondered how it could happen that the learned culture practically never gave an answer to those questions. In music, a lot of interest is paid to similar problems, differently from architecture that never received such an attention from psychology nor from art theoryÂ». This still holds today. Therefore, the question could be: Â«is it still possible today to refer to the communicative resources of the architectural orders for creating meanings through architecture? Diverse replies can be found in the articles of â€œLâ€™Architettura delle cittÃ â€ n. 6, although mutually integrated. The personality of Ludovico Quaroni, to whom the essays of Lucio V. Barbera, Ludovico Micara, Giorgio Muratore and Attilio Petruccioli are dedicated, is itself one of the main integrating elements, as well as the topic of the transformations and new versions of the Classical orders, treated by Antonio Riondino and Anna Irene Del Monaco. In his article, Giorgio Muratore refers about Â«Quaroniâ€™s almost obsessive interest in the question of the architectural order, in its larger sense, not as a simple stylistic derivation of a restricted issue within the larger Vitruvian tradition, but as the guiding principle to a wider logical and structural awareness in creating, conceiving, imagining and designing an architecture envisaged in its consistently specific urban and environmental contextÂ». Based on a fine analysis of the project for the E42 Piazza Imperiale, and demonstrating that Â«starting from 1938 the issue of the architectural order becomes a sort of revenge of a project already compromisedÂ», Attilio Petruccioli rightfully places Ludovico Quaroni Â«in the long-lasting current of refined review of the Classical orderÂ». A never-ending and brilliant architectural research, aiming at a reinterpreting orders, formally and conceptually, â€œto be freerâ€, according to the words of Lucio Valerio Barbera, in his comment to a small, â€œprematureâ€ project for Villa Tuccimei in E42. This process culminates into the capability of penetrating a cultural environment clearly distant from Classical Antiquity, as in the project for the Mosque and the Islamic Cultural Centre in Rome. In all these projects the classical language (John Summerson, 1963) of the architectural orders is revised and transformed for highlighting specific, although not always evident, features of the work. The way these interpretations, based upon in-depth theoretical studies, result meaningful to connote some specific moments of the recent Italian architectural panorama, as the Novecento, is shown by Antonio Riondino. Anna Irene Del Monaco, illustrating the project of Norman Foster for the Nimeâ€™s CarrÃ©e dâ€™Art, draws attention to the peculiar approach of the British culture to the subject of the architectural order. The topic of architectural order is constantly present, even if in a cryptic and intermittent way, in Quaroniâ€™s thought and work, as well as an other presence, not always explicit, but frequently recurring and emerging in particular moments of his activity. It is the case of Quaroniâ€™s first publication, Lâ€™architettura delle cittÃ , written in 1939 and often mentioned in this issue of the homonymous Journal. I frequently wondered about the particular character of this book, his first one. Considering the date of publication, the cultural moment and the contemporary commitment on the project for the E42 Piazza Imperiale, I would have expected from Quaroni, dealing with the ancient city, a study on the classic Graeco-Roman city and architecture. But the book, probably prospecting a second volume, collects and comments on pictures, drawings, plans and archaeological reconstructions of cities of the urban pre-classic cultures. Many of these images, however, could be part of an architecture without architects (Bernard Rudowski, 1964), or, better, of a town planning without town planners, still to be written. Â Quaroni writes, indeed: Â«as regards the environment and what the environment commands to the building, was, most unconsciously, felt by the architect in designing and realizing his work. The environment started to be part of the composition. On the other hand, the discipline today called town planning, that studies the city as a living being, did not try to study, up to now, the character and features of that living being, perhaps due to juvenile inexperience... If it just were the field of studies to suffer for that, it would be negligible; but it is the very city, committed by profanes to town planners and art scholars, that mainly suffersÂ». The young Quaroni was certainly enchanted by the images of Lâ€™architettura delle cittÃ , that illustrate a real golden age of urban planning. When we read the careful comments Quaroni makes to these images, later proposed in a more general way in La torre di Babele (1967), the final object of his research, wished and no more secret, emerges. Â«As a composition the city is... Â». In June 1755 an obscure provincial librarian, Johann Joachim Winckelmann, publishes at hisâ€™ own expenses an anonymous and small booklet, Gedancken Ã¼ber die Nachahmung der griekischen Werke in der Mahlerei und Bildhauer-Kunst (Thoughts on the Imitation of Greek Works in Painting and Sculpture) for the publisher HagenmÃ¼ller of Friedrichstadt (Dresden), in a very limited edition (50 copies). The â€œbookletâ€, containing in nuce the maturityâ€™s works, Geschichte der Kunst des Altertums (History of Art of Antiquity, 1764) and Monumenti antichi inediti (Unpublished Ancient Monuments, 1767) obtained such an immediate success that a second edition was already published in 1756. The research on the origins of beauty in the Greek antiquity, not only passionate, but also lucid and peremptory, was expressed by Winckelmann in the following statements: â€œGood taste, more and more spreading in the world, started to develop at first under the Greek skyâ€. Â«The connoisseurs and imitators of the Greek works find in such masterpieces not just the finest nature, but more than the nature too, as certain ideal beauties resulting, following an old Platoâ€™s disciple, from images only created by the mindÂ». A research that is close, with the obvious differences related to diverse cultural and historical moments, to the intense Quaroniâ€™s work on architectural order and the centrality of ancient city. Returning to J.J.W. Â«what has been said about Homer, admired by people who learned how to appreciate him, is also valid for the masterpieces of the Ancients â€¦ We must know them the way we know a friend â€¦Â». This holds also for Quaroni, a post-antique architect, how he liked to define himself against the superficial definition of post-modern, some critics attributed him after his project for the Rome Opera Theatre. For Winckelmann, as well as for Quaroni, to read again and to reconsider the written, designed and built work, means to face the questions his work continuously addresses, without necessarily resolving them once and for all. As a composition the city is â€¦ P.S. Perhaps a casual element, that the mentioned texts of Winckelmann, WÃ¶lfflin and Quaroni have in common, is their being debut works that will markedly affect their careers, as if they were the incipit of later thought developments. Â Â Â Bibliography Ludovico Quaroni, Lâ€™architettura delle cittÃ , Sansaini Editore, Roma, 1939. Ludovico Quaroni, Progettare un edificio. Otto lezioni di architettura, Gabriele Mazzotta editore, 1977. Heinrich WÃ¶lfflin, Prolegomena zu einer Psychologie der Architektur, 1886. Edizione francese: H. WÃ¶lfflin, ProlÃ©gomÃ¨nes Ã une psychologie de lâ€™architecture, introduction de Bruno Queysanne, Editions CarrÃ©, 1996. Winckelmann, Il bello nellâ€™arte. La natura, gli antichi, la modernitÃ , a cura di C. Franzoni, Giulio Einaudi, 2008. Johann Joachim Winckelmann, Pensieri sullâ€™Imitazione, a cura di Michele Cometa, Aesthetica Edizioni, 2014 (1992).